Optimalisasi Keterbukaan Informasi Berbasis Website DPRD Kota Medan Dalam Perspektif Manajemen Islam - Soemitra, Andri; Khairani br Tambunan, Adila (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Public information disclosure is an important aspect of good governance. Law No. 14 Year 2008 on Indonesian Public Information Disclosure limits the public's right to obtain information on public policies. As a regional legislative body, the Medan City Council is expected to optimise the use of information technology, especially websites, as a tool to provide information to the public. This research aims to analyse the use of DPRD's website in providing information to the public. This research uses descriptive qualitative method with interviews and observations. The results show that the Medan City DPRD website contains various information, such as meeting agendas, decisions, and activity reports. However, there are some shortcomings regarding data update and ease of access. The public has difficulty getting the latest information because some important documents are not updated regularly. In addition, the public is less engaged in providing comments or questions, despite the availability of the DPRD website. Many people are not aware of the interaction features available on the website, such as the discussion forum or complaints column. Public participation should be encouraged through digital platforms to increase public involvement in the decision-making process. This research recommends regular content updates, presentation of more interesting information, and public education on website features to increase engagement. From an Islamic management perspective, accountability and transparency are key to building public trust. The application of Islamic management principles such as tawhid, amanah, justice, transparency and responsibility is expected to improve the effectiveness of public services and strengthen the relationship between DPRD and the community. Optimisation of the website as a platform for interaction and delivery of clear and accurate information is essential to achieve these goals.